Endless Run Based Medicinal Plant Educational Game Development - Yazir, M Sofwan; Tosida, Eneng Tita; Karlitasari, Lita (iora, 2022)
Medicinal plants are very beneficial for health. Medicinal plants can be used as an alternative to cheap and efficient medicine, but not everyone knows what plants can be used as medicine and how to process them. Students are expected to be more familiar with the types of medicinal plants, both local and scientific names, uses, parts used, processing methods, and rules for use. To be able to introduce medicinal plants more interactively, then one solution that can be applied is through application-based games. Educational games are expected to stimulate students to be more active in studying medicinal plants. The game technique used is endless run. Game